1997
DOI: 10.1103/physrevb.56.4925
|View full text |Cite
|
Sign up to set email alerts
|

Electron-stimulated desorption of D+from D2O ice: Surface structure and electronic excitations

Abstract: We present a study of the electron-stimulated desorption of deuterium cations ͑D ϩ) from thin ͑1-40 ML͒ D 2 O ice films vapor deposited on a Pt͑111͒ substrate. Measurements of the total yield and velocity distributions as a function of temperature from 90 to 200 K show that the D ϩ yield changes with film thickness, surface temperature, and ice phase. We observe two energy thresholds for cation emission, near 25 and 40 eV, which are weakly dependent upon the ice temperature and phase. The cation time-of-flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 68 publications
5
54
0
Order By: Relevance
“…The primary electronic excitations which lead to this H + desorption have been assigned to two-hole-one-electron and/or twohole-two-electron configurations. Another ESDthreshold was observed at 40 eV [3]. Souda has examined ESD of (D 2 O) n D + [n = 1-10] from D 2 O clusters adsorbed on rare gas solids and has interpreted that the desorption of the clusters is due to Coulombic expulsion between valence holes in the water cluster [7,8] and his coworkers reported the desorption of (H 2 O) n H + [n = 1-8] from ice surface (>50 ML) [9].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The primary electronic excitations which lead to this H + desorption have been assigned to two-hole-one-electron and/or twohole-two-electron configurations. Another ESDthreshold was observed at 40 eV [3]. Souda has examined ESD of (D 2 O) n D + [n = 1-10] from D 2 O clusters adsorbed on rare gas solids and has interpreted that the desorption of the clusters is due to Coulombic expulsion between valence holes in the water cluster [7,8] and his coworkers reported the desorption of (H 2 O) n H + [n = 1-8] from ice surface (>50 ML) [9].…”
Section: Introductionmentioning
confidence: 95%
“…A variety of studies have been made on electron-and photon-stimulated desorption (ESD/ PSD) at ice surface [1][2][3][4][5][6]. It was reported that the threshold for ESD of H + from ice surface was near 21 eV [1,2].…”
Section: Introductionmentioning
confidence: 98%
“…2 2 1,3 1 (Kimmel & Orlando 1996;Sieger et al 1997;Simpson et al 1997Simpson et al , 1998 were identified as products of the 2 B 1 DEA resonance with a threshold of ∼5.5 eV and peak around 7 eV for a 10 ML amorphous ice film. These DEA channels may play important roles in radical (O and OH) production at the buried graphite-ice interface.…”
Section: Co/co 2 Formation At the Buried Interfacementioning
confidence: 99%
“…In order to reveal the dynamics of electronic excited state of water molecules, the mechanism of desorption induced by electronic transitions (DIET) of cations [5][6][7][8][9][10][11], anions [12][13][14][15] and neutrals [16,17] from condensed or adsorbed H 2 O has been investigated by several groups.…”
Section: Introductionmentioning
confidence: 99%
“…Seiger and his coworkers [7] found desorption thresholds for electron-stimulated desorption (ESD) of D + from D 2 O ice near 22 and 40 eV. The primary electronic excitations which lead to this desorption have been assigned to several two-hole one-electron and two-hole two-electron configurations, whose states are dissociative, and the kinetic energy of the proton is likely to be generated by the Coulomb repulsion of the hole pair in a water molecule.…”
Section: Introductionmentioning
confidence: 99%